Modeling anthropogenic noise propagation using the Sound Mapping Tools ArcGIS toolbox. (November 2017) - Keyel, Alexander C.; Reed, Sarah E.; McKenna, Megan F.; Wittemyer, George
Abstract: We introduce the open-source Sound Mapping Tools (SMT, implemented in ArcGIS with the Spatial Analyst extension) for use in terrestrial outdoor sound propagation modeling. SMT includes three sound propagation models: an updated version of SPreAD-GIS, based on the System for Prediction of Acoustic Detectability model; NMSIMGIS, a GIS implementation of the Noise Model Simulation (NMSim) algorithms; and an implementation of an international outdoor sound propagation standard, ISO 9613–2. SMT produces spatially-explicit predictions of sound pressure levels from one or more sound sources, facilitating the assessment of noise effects from sources such as motorized recreation, energy development, and road traffic. Model results can be weighted to represent variable acoustic sensitivity or compared to ambient sound pressure levels. SMT provides a user-friendly approach to produce sound level predictions across variable landscapes, with applications for environmental, behavioral, population, and community ecology studies and for planning and management of human land use and infrastructure. Highlights: Sound Mapping Tools (SMT) can be used for terrestrial sound propagation modeling. SMT contains three models, SPreAD-GIS, NMSIMGIS, and ISO 9613-2. Models can assess potential impacts of noise on ecosystems and human health. Recreation, energy development and traffic noise can be modeled.